2019
DOI: 10.3389/fchem.2019.00425
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mn2+ on Upconversion Emission, Thermal Sensing and Optical Heater Behavior of Yb3+ - Er3+ Codoped NaGdF4 Nanophosphors

Abstract: In thiswork, we investigate the influence of Mn 2+ on the emission color, thermal sensing and optical heater behavior of NaGdF 4 : Yb/Er nanophosphors, which the nanoparticles were synthesized by a hydrothermal method using oleic acid as both a stabilizing and a chelating agent. The morphology and crystal size of upconversion nano particles (UCNPs) can be effectively controlled through the addition of Mn 2+ dopant contents in NaGdF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 65 publications
3
18
0
Order By: Relevance
“…This trend was reflected in a shift towards higher 2θ angles for all samples between 0 and 35 mol% Mn 2+ , with a similar reversal for 40% Mn 2+ (see electronic supplementary material, figure S8c,d,f,g,h). Similar shifts in 2θ angle have been reported for upconversion materials co-doped with Fe 3+ and Mn 2+ [55,[57][58][59][60].…”
Section: Resultssupporting
confidence: 83%
“…This trend was reflected in a shift towards higher 2θ angles for all samples between 0 and 35 mol% Mn 2+ , with a similar reversal for 40% Mn 2+ (see electronic supplementary material, figure S8c,d,f,g,h). Similar shifts in 2θ angle have been reported for upconversion materials co-doped with Fe 3+ and Mn 2+ [55,[57][58][59][60].…”
Section: Resultssupporting
confidence: 83%
“…In general, information about the thermometric performance (thermal sensitivity, S r ) of the upconverting nanosensors is inferred from the fluorescence intensity ratio (Δ) of thermally coupled energy levels of the Ln 3+ ions. Several studies have reported that the thermometric parameter Δ, appears to be reliant on the type of host, type of dopant ion and their concentrations, , size of the nanoparticles, , surface functionalization, core–shell structure, , incorporation of transition metals, laser excitation density, and modification of the energy transfer processes (Table ). As such, detailed studies involving optimization of the chemical and spectroscopic properties of UCNP-based sensors have been performed to increase the operating temperature sensitivity and temperature resolution to fulfill the specific needs of given applications.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the photo-luminescence of rare earth is extremely stable, and it could not be affected by blinking or photobleaching ( Shao et al, 2018 ; Song et al, 2019 ). These advantages make rare earth elements perfect candidates for light-triggered diagnostics and therapy ( Chen et al, 2014 ; Shao et al, 2016 ; Qiang and Wang, 2019 ; Wang et al, 2020 ). As an unusual anti-stokes process, photon upconversion (UC) refers to converting several low-energy photons to one high-energy photon ( Zhou et al, 2015 ; Wei et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%